191k views
7 votes
Solve the equation

2(h-8) - h=h - 16

A h = 8

B h= -8

C h = infinitely many solutions

D h = no solution

2 Answers

8 votes

Answer:

C h= infinitely many solutions

Explanation:

when you replace h with any number it is true

say h= 3

2(3-8) - h = h-16

2(-5) - 3 = 3 - 16

-10 - 3 = -13

-13 = -13

using distributive property:

2h-16-h = h-16

combine like terms

h-16=h-16

it is the same expression on both sides of the equal sign

hope that helps!

User Danny Hong
by
4.5k points
12 votes

Answer:

2(h-8)-h=h-16

2(h-8)=h+h-16

2(h-8)=2h-16

2(h-8)=2(h-8)

h-8=h-8

h-h=8-8

0=0 so their can be infinite value of h.

hence c is correct

we can put in place of anything but answer will be zero.

User Roel Van De Paar
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.